A Study of Industry Cost of Equity in Australia Using the Fama and French 5 Factor Model and the Capital Asset Pricing Model (CAPM): A Pitch - Will Mackay; Tariq Haque (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This paper describes the use of the Faff (2015) pitching template to formulate a research concept into a formal research proposal. It outlines our experience in applying the various sections of the pitch template and the challenges experienced in doing so. Overall the adoption of the pitch template has significantly improved our approach to developing research projects.
Keywords: G12; G28; 650; Pitching research; FFM5; Regulated Energy Sector; CAPM